ALL-090 Highly Effective Combination of FLT3 and BCL2 Inhibitors in a Preclinical Model of Lineage Ambiguous Leukemia - Montefiori, Lindsey; lacobucci, Ilaria; Budhraja, Amit; Moore, Jamila; Baskin, Rebekah; DeVries, Rebekah; Backhaus, Emily; Johnson, Melissa; Akers, Walter; Chepyala, Divyabharathi; Mehr, Cyrus; Seth, Aman; et al. (Clinical lymphoma, myeloma and leukemia, 2022)
Context: Lineage ambiguous leukemias are rare leukemia subtypes with diagnostic and treatment challenges and poor outcomes. We recently described a new subtype of lineage ambiguous leukemia defined by aberrant BCL11B activation (“BCL11B-a”) which included 30%–40% of T/myeloid mixed-phenotype acute leukemia (MPAL) and early T-cell precursor acute lymphoblastic leukemia (ETP-ALL) cases, as well as 8% of acute myeloid leukemia cases (Montefiori et al. Cancer Discovery 2021). Most cases (81%) harbored activating FLT3 mutations, and all showed high FLT3 expression in addition to significantly higher BCL2 expression than non-BCL11B-a cases, suggesting a therapeutic vulnerability. Objective: To determine the efficacy of FLT3 and BCL2 inhibitors in treating BCL11B-a lineage ambiguous leukemia. Results: Here, we treated a BCL11B-a patient-derived xenograft (PDX) (original diagnosis of T/myeloid MPAL, FLT3-ITD positive) with the FLT3 inhibitor gilteritinib and the BCL2 inhibitor venetoclax, either alone or in combination. Treating commenced once disease burden reached at least 108 p/sec/cm2/sr (radiance) by whole-body imaging and continued for 8 weeks. Single-agent venetoclax exhibited a short-lived effect, whereas gilteritinib monotherapy delayed leukemia growth compared to vehicle (vehicle: 6.5–13×1010 p/sec/cm2/sr; venetoclax: 3.8–7.1×1010 p/sec/cm2/sr; gilteritinib: 3.6–7.4×109 p/sec/cm2/sr at end of treatment). In contrast, combination treatment rapidly and stably reduced leukemic burden to pre-treatment levels (8.8×105–1.1×107 p/sec/cm2/sr at end of treatment). Despite this near clearance of disease in combination-treated animals, leukemia burden increased following drug removal, indicating the capacity of the disease to persist in the presence of sustained combination therapy, although it remained sensitive to re-treatment. Moreover, we demonstrated that gilteritinib+venetoclax effectively reduced leukemia burden in heavily engrafted animals (>1011 p/sec/cm2/sr at start of treatment), suggesting that this combination may be effective at diagnosis in patients with high leukemia burden. Conclusions: Here, we showed that the combination of FLT3 (gilteritinib) and BCL2 (venetoclax) inhibitors is highly effective at reducing leukemia burden in a preclinical model of BCL11B-a lineage ambiguous leukemia. This combination blocked leukemic growth in vivo and was effective in highly engrafted animals. Ongoing studies in additional PDXs and pharmacodynamic work will identify mechanisms of synergy and characterize the residual combination-treated population to better understand putative drug resistance mechanisms.